Export diversification and dependence on natural resources - Zuzanna Zarach; Aleksandra Parteka (Gdańsk University of Technology, Faculty of Management and Economics, 2022)
This paper models export diversification in the context of an abundance of natural resources by decomposing the relative Theil index. On a sample of 160 countries from 1996 to 2018 we document that 74% of the high export concentration typical of the initial stage of development is driven by the limited variety of products other than natural resources. Later, the component representing export reallocation between resources and non-resource products gains importance, and eventually, together with intra-resource heterogeneity, explains the entire amount of export diversification at high income levels. Our estimates show that natural resource abundance (in particular of fossil fuels) impedes overall diversification, limiting the variety of non-resource exports and hampering restructuring towards technologically advanced exports. However, once size and productivity differences across countries are taken into account, the effect of resource abundance on export diversification is weak.
Keywords: F14; O13; Q3; 330; natural resources; export diversification; Theil; decomposition